A phase I/IIa double blind single institute trial of low dose sirolimus for Pendred syndrome/DFNB4. Issue 19 (May 2020) - Fujioka, Masato; Akiyama, Takumi; Hosoya, Makoto; Kikuchi, Kayoko; Fujiki, Yuto; Saito, Yasuko; Yoshihama, Keisuke; Ozawa, Hiroyuki; Tsukada, Keita; Nishio, Shin-ya; Usami, Shin-ichi; Matsunaga, Tatsuo; et al.
Abstract: Introduction: Pendred syndrome (PDS)/DFNB 4 is a disorder with fluctuating and progressive hearing loss, vertigo, and thyroid goiter. We identified pathophysiology of a neurodegenerative disorder in PDS patient derived cochlear cells that were induced via induced pluripotent stem cells and found sirolimus, an mTOR inhibitor, as an inhibitor of cell death with the minimum effective concentration less than 1/10 of the approved dose for other diseases. Given that there is no rational standard therapy for PDS, we planned a study to examine effects of low dose oral administration of sirolimus for the fluctuating and progressive hearing loss, and the balance disorder of PDS by daily monitor of their audio-vestibular symptoms. Methods and analysis: This is a phase I/IIa double blind parallel-group single institute trial in patient with PDS/DFNB4. Sixteen of outpatients with fluctuating hearing diagnosed as PDS in SLC26A4 genetic testing aged in between 7 and 50 years old at the time of consent are given either placebo or sirolimus tablet (NPC-12T). In NPC-12T placebo arm, placebo will be given for 36 weeks; in active substance arm, placebo will be given for 12 weeks and the NPC-12T for 24 weeks. Primary endpoints are safety and tolerability. The number of occurrences and types of adverse events and of side effects will be sorted by clinical symptoms and by abnormal change of clinical test results. A 2-sided 95% confidence interval of the incidence rate by respective dosing arms will be calculated using the Clopper–Pearson method. Clinical effects on audio-vestibular tests performed daily and precise physiological test at each visit will also be examined as secondary and expiratory endpoints. Trial registration number: JMA-IIA00361; Pre-results. Abstract : Supplemental Digital Content is available in the text